CONCENTRATIONS OF HEAVY METALS Pb, Cu AND Zn IN SEDIMENT AND SEA WATER OF TELAGA TUJUH KARIMUN REGENCY RIAU ISLANDS PROVINCE - Bintal Amin; Rifardi '; M. Iqbal A (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
ABSTRACTThe Study was conducted in July 2012 by taking seawater and sediment samples from Telaga Tujuh Karimun Regency of Riau Islands Province . The purpose of this study was to find out the concentration of heavy metals Pb , Cu and Zn in sediment and seawater in the Telaga Tujuh waters and also to see the relationships between heavy metals Pb , Cu and Zn in sea water with Pb , Cu and Zn in the sediment. Sampling locations were determined by purposive sampling method , where 6 station were choose with three replicates. Based on the results it was suggested that Telaga Tujuh waters are still suitable for aquatic organisms living waters . Higher concentrations of Zn on were found when compared to Pb and Cu bouth in seawater or in sediment . Standard Quality Guideline values for metal concentrations in sediment showed that Pb , Cu and Zn in the sediment were very close to the ERL but still well below the ERM values. The concentration of heavy metals Pb , Cu and Zn in sea water were negative by correlated with concentration of heavy metals in the sediments.Keywords : Telaga Tujuh, Heavy Metals, Sediment, Seawater